PEMBERDAYAAN APARAT KELURAHAN DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK (Suatu Studi Di Kecamatan Singkil Kota Manado) - JENILDA PAPUTUNGAN; MARTHA OGOTAN; FEMMY TULUSAN (JURNAL ADMINISTRASI BISNIS, 2014)
ABSTRACT : In the public service, government officials are responsible for providing excellentservice to the community in order to create a welfare society. Society has the right to get the bestservice from the government because the public has provided funds in the form of payment of levies.Under these conditions, this study to determine the extent to which the relationship between theempowerment of village officials with the quality of public services in the city of Manado Singkildistricts.This study used a quantitative approach with a descriptive and explanatory methods. This ispossible because on one side of the problem carefully enough at the actual and on the other hand, thisstudy intends to analyze between the two variables. Source of data / research respondents as many as64 people taken from public officials and employees. To analyze the relationship between the twovariables used product moment correlation analysis.Once the analysis is calculated with SPSS version 20 for windows then obtained a coefficient of 0.959.So there is a positive relationship between empowerment of village officials with the quality of publicservices.Based on the results of the data analysis deduced that, after doing the research variablesidentifying the distribution of respondents' answers to the average of all the variables are in the highcategory. Thus, the proposed hypothesis has been tested empirically once enforceability justify theunderlying theories.Keywords: Empowerment of village officials with the quality of service